Association Between the Risk for Cardiovascular Events and Antiviral Treatment for Herpes Zoster. (14th September 2020) - Kim, Jinkwon; Jeon, Jimin; Lee, Hye Sun; Lee, Kyung-Yul
Abstract: Background: Cardiovascular risk increases following herpes zoster. We investigated whether treatment with antiviral agents, steroids, and common cardiovascular medications was associated with the risk of postherpetic cardiovascular events. Methods: This was a nationwide population-based, retrospective, cohort study using the National Health Insurance Service health claims data in Korea. We included patients with a first-ever diagnosis of herpes zoster in 2003–2014 and no prior cardiovascular event. The primary outcome was the occurrence of composites of myocardial infarction ( International Statistical Classification of Diseases, Tenth Revision, code I21) and stroke (codes I60–I63) since the herpes zoster. We analyzed the exposure (intravenous or oral administration) to antiviral agents, steroids, antithrombotics, and statins within ±7 days from the index date of herpes zoster diagnosis. Follow-up was performed until occurrence of the primary outcome, death, or 31 December 2015, whichever came first. Results: Of 84 993 patients with herpes zoster, the proportions of patients who received the treatment with antiviral agents, steroids, antithrombotics, and statins were 90.5%, 48.0%, 9.1%, and 7.9%, respectively. During the mean (standard deviation) follow-up period of 5.4 (3.1) years, 1523 patients experienced the primary outcome. Multivariate Cox regression analysis demonstrated that treatment with antiviral agents (adjusted hazard ratio, 0.82; 95% confidence interval, .71–.95) and statins (0.71; .59–.85) were significantly associated with the lower risk of primary outcome. Use of antithrombotics and steroids were not associated with the risk. Conclusions: After herpes zoster, treatment with antiviral agents was significantly associated with lower risk of cardiovascular events. We need more information on the cardiovascular protective role of herpes zoster treatments. Abstract : We evaluated the risk for stroke and myocardial infarction after herpes zoster, according to treatment with antiviral agents. In patients with herpes zoster, use of antiviral agents was significantly associated with lower risk of cardiovascular events.